1997
DOI: 10.1074/jbc.272.24.15396
|View full text |Cite
|
Sign up to set email alerts
|

Coordinate Expression of α-Tropomyosin and Caldesmon Isoforms in Association with Phenotypic Modulation of Smooth Muscle Cells

Abstract: Isoform diversity of tropomyosin is generated from the limited genes by a combination of differential transcription and alternative splicing. In the case of the ␣-tropomyosin (␣-TM) gene, exon 2a rather than exon 2b is specifically spliced in ␣-TM-SM mRNA, which is one of the major tropomyosin isoforms in smooth muscle cells. Here we demonstrate that expressions of ␣-tropomyosin and caldesmon isoforms are coordinately regulated in association with phenotypic modulation of smooth muscle cells. Molecular cloning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
45
1

Year Published

1998
1998
2008
2008

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 55 publications
2
45
1
Order By: Relevance
“…Although more detailed studies are required, our results suggested that the 41 kDa tropomyosin monomer plays an important role in contraction. Regarding the interaction between tropomyosin and caldesmon, coincident expression of α-tropomyosin and caldesmon isoforms in SMCs has been reported (Kashiwada et al, 1997). While the present result on tropomyosin is similar, studies at the mRNA level and on the relationship between caldesmon isoforms are required before the role of tropomyosin isoforms can be understood.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Although more detailed studies are required, our results suggested that the 41 kDa tropomyosin monomer plays an important role in contraction. Regarding the interaction between tropomyosin and caldesmon, coincident expression of α-tropomyosin and caldesmon isoforms in SMCs has been reported (Kashiwada et al, 1997). While the present result on tropomyosin is similar, studies at the mRNA level and on the relationship between caldesmon isoforms are required before the role of tropomyosin isoforms can be understood.…”
Section: Discussionsupporting
confidence: 60%
“…If culture conditions were achieved which kept the SMCs in their differentiated state as reported for other SMCs (Bowers and Dahm, 1993;Kashiwada et al, 1997;Ma et al, 1998;Halayko et al, 1999), protein isoform changes during culture may be expected to be different from those in this study. The differences would provide important information about the role of each isoform of the contractile proteins and of the contraction mechanism of SMCs.…”
Section: Discussionmentioning
confidence: 63%
“…as SMC-differentiation molecular markers (21). The chicken ␤-TM gene contains muscle and non-muscle promoters, and both smooth (␤-TMsm) and skeletal (␤-TMsk) muscle isoforms are transcribed from the same muscle promoter (22).…”
Section: /Ebi Data Bank With Accession Number(s) Ab044371 (Chicken Bamentioning
confidence: 99%
“…20,21 Although a number of smooth muscle specific proteins undergo such a differentiationdependent isoform switchover, including actin, 22 myosin heavy chain, 23 calponin, 24 vinculin 25 and Tm, 26 the expression of CaD and Tm are probably most closely related to each other. In fact, the same splicing machinery appears to work on both CaD and Tm, as the two α-Tm isoforms (α-Tm-SM or Tm6 and α-Tm-F1/2 or Tm2; for Tm nomenclature, see Gunning et al 27 ) are expressed in a tightly coordinated fashion with the two isoforms of CaD both in vivo and in vitro.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the same splicing machinery appears to work on both CaD and Tm, as the two α-Tm isoforms (α-Tm-SM or Tm6 and α-Tm-F1/2 or Tm2; for Tm nomenclature, see Gunning et al 27 ) are expressed in a tightly coordinated fashion with the two isoforms of CaD both in vivo and in vitro. 26,28 Interestingly, when cells were forced to express Tm1 but not Tm2, there was also an up-regulation of CaD expression. 29 It has been shown that a serum response factor (SRF) is necessary but not sufficient to transactivate the CaD promoter.…”
Section: Introductionmentioning
confidence: 99%